A Critical Evaluation of Current Methods for Exercise Prescription in Women and Men. Issue 2 (February 2020) - IANNETTA, DANILO; INGLIS, ERIN CALAINE; MATTU, ANMOL T.; FONTANA, FEDERICO Y.; POGLIAGHI, SILVIA; KEIR, DANIEL A.; MURIAS, JUAN M.
ABSTRACT: Common methods to prescribe exercise intensity are based on fixed percentages of maximum rate of oxygen uptake (V˙O2max ), peak work rate (WRpeak ), maximal HR (HRmax ). However, it is unknown how these methods compare to the current models to partition the exercise intensity spectrum. Purpose: Thus, the aim of this study was to compare contemporary gold-standard approaches for exercise prescription based on fixed percentages of maximum values to the well-established, but underutilized, "domain" schema of exercise intensity. Methods: One hundred individuals participated in the study (women, 46; men, 54). A cardiopulmonary ramp-incremental test was performed to assess V˙O2max, WRpeak, HRmax, and the lactate threshold (LT), and submaximal constant-work rate trials of 30-min duration to determine the maximal lactate steady-state (MLSS). The LT and MLSS were used to partition the intensity spectrum for each individual in three domains of intensity: moderate, heavy, and severe. Results: V˙O2max in women and men was 3.06 ± 0.41 L·min −1 and 4.10 ± 0.56 L·min −1, respectively. Lactate threshold and MLSS occurred at a greater %V˙O2max and %HRmax in women compared with men ( P < 0.05). The large ranges in both sexes at which LT and MLSS occurred on the basis of %V˙O2max (LT, 45%–74%; MLSS, 69%–96%), %WRpeak (LT, 23%–57%; MLSS, 44%–71%), and %HRmax (LT, 60%–90%; MLSS, 75%–97%) elicited large variability in the number of individuals distributed in each domain at the fixed-percentages examined. Conclusions: Contemporary gold-standard methods for exercise prescription based on fixed-percentages of maximum values conform poorly to exercise intensity domains and thus do not adequately control the metabolic stimulus.